HUBUNGAN PERSEPSI SISWA TENTANG LINGKUNGAN BELAJAR BERBASIS TEKNOLOGI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN SISTEM KOMPUTER KELAS X BIDANG TEKNOLOGI DI SMK N 1 SIJUNJUNG - Edri Faldo; Adlia Alfiriani; Irsyadunas (STMIK KAPUTAMA, 2023)
The aims of this study are know students' perceptions of the technology-based learning environment at SMK N 1 Sijunjung. Knowing how student learning outcomes in the subject of computer systems. Knowing the relationship between students' perceptions of the technology-based learning environment on student learning outcomes in computer systems subjects.This study used a quantitative research approach in the form of numbers and statistical analyzes which were carried out by collecting data and using a structured questionnaire (questionnaire) which was compiled based on measurements of the variables studied which then produced quantitative data. Results obtaineddata obtained from a questionnaire on student perceptions of the technology-based learning environment at SMK N 1 Sijunjung, that student perceptions of the learning environment on the learning conditions indicator were 64.79% in the good category. teaching method of 54.75%, teacher-student relations of 65.64% with a good category of student learning outcomes, the average student learning outcomes in the subject of computer systems is 75.92.